Euglena gracilis-derived β-glucan paramylon entrains the peripheral circadian clocks in mice - Ryan, Conn; Cao, Siyuan; Sekiguchi, Masataka; Haraguchi, Atsushi; Murata, Ako; Nakashima, Ayaka; Suzuki, Kengo; Shibata, Shigenobu (Frontiers in Nutrition, 2023)
Paramylon, a β-1,3-glucan storage polysaccharide derived from Euglena gracilis, has various health benefits, such as anti-obesity effects and modulation of immune function. However, whether paramylon intake affects the circadian clock remains unknown. In this study, we examined the effect of paramylon intake on the circadian clock. The results showed that the paramylon intake regulated peripheral clocks in mice. Furthermore, cecal pH and short-chain fatty acid concentrations after paramylon intake were measured. The correlation between changes in the expression of clock-related genes and alterations in the intestinal environment was confirmed. In addition, peripheral clock entrainment by paramylon intake was not observed in antibiotic-treated mice whose gut microbiota was weakened. These findings suggest that the regulation of the circadian clock by paramylon intake was mediated by changes in gut microbiota. In addition, the entraining effect of paramylon intake was also confirmed in mice bred under conditions mimicking social jetlag, which implies that paramylon intake may contribute to recovery from social jetlag. Thus, the appropriate consumption of paramylon may have a beneficial effect on health from a chrononutritional perspective.